Customer Bonding, Customer Satisfaction, and Customer Loyalty (Study on the Customer of “SMEs Martabak Hokky Kawanua” on Tondano) - Steven Set Xaverius Tumbelaka; Jenny Nancy Kaligis; Ericson Mengga (AIBPM Publisher, 2022)
This research was conducted on Martabak Hokky SME customers in Tondano city, with the aim of knowing how the level of influence of Customer Bonding to Customer Loyalty, and the influence of Customer Satisfaction to Customer Loyalty, especially in the SMEs we studied, in addition to that, this research will also look at the joint influence of Customer Bonding and Customer Satisfaction on Customer Loyalty from the SMEs studied. Quantitative method with multiple regression analysis is the method and analysis that is the choice to be used in this study, by taking a sample of 1 10 people. The findings from the multiple analysis test obtained from the study, show that there is a significant effect of Customer Bonding to Customer Loyalty, it can be explained that good Customer Bonding will help increase Loyalitas Customer significantly. The next result also shows a partially significant influence of Customer Satisfaction to Customer Loyalty, so it can be said that if Customer Satisfaction increases, it will also increase Loyalty as Customers significantly as well, The final results of the study show The simultaneous significant influence from Customer Bonding and Customer Satisfaction to Customer Loyalty from SMEs studied in this study, in other words, the increase in customer loyalty is strongly influenced by the better Customer Bonding and Customer Satisfaction. It can be suggested to the manager of Martabak UKM Hokky Kawanua to be able to pay better attention to how to maintain Customer Bonding and Customer Satisfaction in order to be able to continue to form loyalty from strong customers, so that customers will continue to buy products, and for further research to be able to see and test more deeply about customer loyalty by paying attention to other variables that were not studied in this study.